STRATEGI PENGEMBANGAN PARIWISATA KABUPATEN SUMBAWA (Studi Pada Kawasan Samota) - S Suprianto; I Ismawati; Nurwahidah Aprilia (Pusat Riset dan Publikasi, 2021)
This study aims to know the right strategy in the developing SAMOTA tourism area in Sumbawa District. This study was field study and the approach used were mix method namely both qualitative and quantitative method. Data collection methods used in this study were interviews, questionnaires, and documentation. The analytical method used was SWOT analysis to know the strengths, weaknesses, opportunities and threats of Samota tourism area in Sumbawa District. The results of study showed that the Samota had very large potential of natural resources, besides that it was also supported by the designation of SAMOTA as a biosphere reserve by UNESCO, but the Treat of SAMOTA Area were that its development has not been able to be optimized, the less awareness of the societies, and the condition of infrastructure or facilities that were not sufficient.To optimize its development, it is need right strategy namely by increasing promotion by utilizing technology, improving facilities and infrastructure and supporting infrastructure, increasing public awareness, and improving the quality of Human Resources.